2007
DOI: 10.2353/ajpath.2007.060898
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Leukoencephalopathy with Widespread Astrogliosis in Mice Lacking Transcription Factor Nrf2

Abstract: NFE2-related factor 2 (Nrf2), an oxidant-activated CNC bZip transcription factor, has been implicated in defense against oxidative stress and chemical insults in a range of cell and tissue types, including the central nervous system. Here, we report that deletion of the Nrf2 gene in mice caused vacuolar (spongiform) leukoencephalopathy with widespread astrogliosis. The leukoencephalopathy was present in all Nrf2-null mice more than 10 months of age, was characterized by vacuolar degeneration involving all majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 28 publications
(36 reference statements)
1
78
0
1
Order By: Relevance
“…However, due to the lack of direct biochemical evidence of phosphorylation of the Nrf2 protein, the role and mechanism of phosphorylation in Nrf2 regulation remain elusive. We have previously reported that ablation of Nrf2 induces leukoencephalopathy with widespread gliosis in the mouse brain suggesting a physiological function of Nrf2 in neuronal cells of the central nervous system (CNS) origin [20]. In this report, we observed that tBHQ stabilized two forms of Nrf2 protein in neuroblastoma cells (IMR-32) that migrates distinctively in SDS-PAGE gels; the slower migrating form was identified as phosphorylated Nrf2, whereas the faster form corresponded to nonphosphorylated protein of Nrf2.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, due to the lack of direct biochemical evidence of phosphorylation of the Nrf2 protein, the role and mechanism of phosphorylation in Nrf2 regulation remain elusive. We have previously reported that ablation of Nrf2 induces leukoencephalopathy with widespread gliosis in the mouse brain suggesting a physiological function of Nrf2 in neuronal cells of the central nervous system (CNS) origin [20]. In this report, we observed that tBHQ stabilized two forms of Nrf2 protein in neuroblastoma cells (IMR-32) that migrates distinctively in SDS-PAGE gels; the slower migrating form was identified as phosphorylated Nrf2, whereas the faster form corresponded to nonphosphorylated protein of Nrf2.…”
Section: Introductionmentioning
confidence: 73%
“…We have previously reported that mice with Nrf2-deficiency developed spongiform leukoencephalopathy with extensive astrogliosis in the brain, implicating important roles of Nrf2 in CNS function under physiological conditions [20]. To characterize Nrf2 in neuronal cells of CNS origin, we examined Nrf2 signaling in neuroblastoma (IMR-32) cells.…”
Section: Phosphorylation Of Nrf2 Results In a Slower Migrating Form Omentioning
confidence: 99%
“…nrf2 Ϫ/Ϫ mice display vacuolar leukoencephalopathy, which is characterized by vascular degeneration involving all major brain regions. In white tracts, the vascular degeneration is accompanied by widespread reactive gliosis (47). Finally, preliminary data suggest that the development of experimental autoimmune encephalomyelitis, which is an experimental model of multiple sclerosis, is exacerbated in nrf2 Ϫ/Ϫ , mice suggesting a possible role of the Nrf2-ARE pathway in the pathogenesis of multiple sclerosis (48).…”
Section: Nrf2-are Pathway As a Therapeutic Target For Treatment Of Nementioning
confidence: 99%
“…17 Although deletion of Bach2 in mice caused impaired antibody class switching, 18 disruption of Nrf2 resulted in a neurodegenerative disorder and autoimmune disease. [19][20][21] Deciphering the physiologic role of some of the CNC/Maf proteins has also proven to be challenging because of the potential functional redundancy among them. 22,23 The CNC/Maf network has been associated with a myriad of human disorders, including those of the skin, respiratory system, and hematopoietic system.…”
Section: Introductionmentioning
confidence: 99%